PERANAN HUKUM DALAM MENGATASI POTENSI ECONOMIC LEAKAGE AKIBAT KENAIKAN CUKAI ROKOK PASCA PEMBERLAKUAN PERATURAN MENTERI KEUANGAN NOMOR 97 TAHUN 2024 - Putri Balqis Ar Rodhiah; Detania Sukarja; Tri Murti Lubis (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The policy of increasing tobacco excise tariffs through Minister of Finance Regulation Number 97 of 2024 constitutes a fiscal instrument aimed at increasing state revenue and controlling cigarette consumption. However, the policy also has the potential to increase the circulation of illegal cigarettes, which may lead to economic leakage in the form of reduced state revenue from the excise sector. This study aims to analyze the legal framework for excise law enforcement against the circulation of illegal cigarettes, examine the effectiveness of law enforcement in addressing the potential for economic leakage, and identify the obstacles to law enforcement following the enactment of Minister of Finance Regulation Number 97 of 2024. This research employs a normative-empirical legal method using statutory, conceptual, and empirical approaches. Data were obtained through literature study and interviews with the Directorate General of Customs and Excise. The analysis was conducted descriptively and analytically to assess the effectiveness of the implementation of excise regulations in supervising and prosecuting illegal cigarette circulation. The results of the study indicate that the legal framework for excise enforcement in Indonesia has been comprehensively regulated through Law Number 39 of 2007 concerning Excise and its implementing regulations, including Minister of Finance Regulation Number 97 of 2024. However, the implementation of law enforcement has not been fully optimal due to weak distribution supervision, limited law enforcement resources, and suboptimal inter-agency coordination. The increase in excise tariffs has also contributed to a shift among certain consumers toward cheaper illegal cigarettes, thereby increasing the risk of economic leakage and reducing the effectiveness of the state's fiscal policy. In addition, the extensive supervisory area and the complexity of cigarette distribution chains constitute major challenges in eradicating illegal cigarettes. Therefore, stronger supervision of tobacco product distribution, improved coordination among law enforcement agencies, and the optimization of preventive and repressive strategies are necessary to suppress the circulation of illegal cigarettes and minimize the potential for economic leakage resulting from increases in cigarette excise tariffs.